Hypothermia combined with neuroprotective adjuvants shortens the duration of hospitalization in infants with hypoxic ischemic encephalopathy: Meta-analysis - Ovcjak, Andrea; Pontello, Riley; Miller, Steve P.; Sun, Hong-Shuo; Feng, Zhong-Ping (Frontiers in Pharmacology, 2023)
Objective: Therapeutic hypothermia (TH) is the current standard of care for neonatal hypoxic-ischemic encephalopathy (HIE), yet morbidity and mortality remain significant. Adjuvant neuroprotective agents have been suggested to augment hypothermic-mediated neuroprotection. This analysis aims to identify the classes of drugs that have been used in combination with hypothermia in the treatment of neonatal HIE and determine whether combination therapy is more efficacious than TH alone. Methods: A systematic search of PubMed, Embase and Medline from conception through December 2022 was conducted. Randomized- and quasi-randomized controlled trials, observational studies and retrospective studies evaluating HIE infants treated with combination therapy versus TH alone were selected. Primary reviewers extracted information on mortality, neurodevelopmental impairment and length of hospitalization for meta-analyses. Effect sizes were pooled using a random-effects model and measured as odds ratio (OR) or mean difference (MD) where applicable, and 95% confidence intervals (CI) were calculated. Risk of bias was assessed using the tool from the Cochrane Handbook for Systematic Reviews of Interventions. Results: The search strategy collected 519 studies, 16 of which met analysis inclusion criteria. HIE infants totaled 1,288 infants from included studies, 646 infants received some form of combination therapy, while 642 received TH alone. GABA receptor agonists, NMDA receptor antagonists, neurogenic and angiogenic agents, stem cells, glucocorticoids and antioxidants were identified as candidate adjuvants to TH that have been evaluated in clinical settings compared to TH alone. Length of hospitalization was significantly reduced in infants treated with combination therapy (MD −4.81, 95% CI [−8.42. to −1.19], p = .009) compared to those treated with TH alone. Risk of mortality and neurodevelopmental impairment did not differ between combination therapy and TH alone groups. Conclusion: Compared to the current standard of care, administration of neuroprotective adjuvants with TH reduced the duration of hospitalization but did not impact the risk of mortality or neurodevelopmental impairment in HIE infants. Meta-analysis was limited by a moderate risk of bias among included studies and small sample sizes. This analysis highlights the need for preclinical trials to conduct drug development studies in hypothermic settings to identify relevant molecular targets that may offer additive or synergistic neuroprotection to TH, and the need for larger powered clinical trials to determine the dose and timing of administration at which maximal clinical benefits are observed for adjuvant neuroprotectants.